1997
DOI: 10.1901/jeab.1997.68-67
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Extension of Equivalence Classes From Primary Generalization Gradients: The Merger of Equivalence Classes and Perceptual Classes

Abstract: In Experiment 1, 6 college students were given generalization tests using 25 line lengths as samples with a long line, a short line, and a "neither" option as comparisons. The neither option was to be used if a sample did not go with the other comparisons. Then, four-member equivalence classes were formed. Class 1 included three nonsense words and the short line. Class 2 included three other nonsense words and the long line. After repeating the generalization test for line length, additional tests were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
65
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 67 publications
6
65
0
Order By: Relevance
“…Consistent with preVious studies (Fields et aI., 1991;1997), this experiment demonstrated the generalization of equivalence relations to dimensional variants of class members. This procedure differed from those in previous studies in showing generalization along the dimension of hue, and in showing the generalization of relations involving stimuli which had been presented as elements of complex samples during training.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with preVious studies (Fields et aI., 1991;1997), this experiment demonstrated the generalization of equivalence relations to dimensional variants of class members. This procedure differed from those in previous studies in showing generalization along the dimension of hue, and in showing the generalization of relations involving stimuli which had been presented as elements of complex samples during training.…”
Section: Discussionsupporting
confidence: 86%
“…It was found that as the physical disparity between dimensional variants and class members systematically increased, the proportion of class-consistent responses declined (see also Fields, Reeve, Adams, & Verhave, 1991;and Fields, Adams, Buffington, Yang, & Verhave, 1996). Fields, Reeve, Adams, Brown, and Verhave (1997) used generalization gradients obtained prior to an equivalence test to predict to which dimensional variants stimulus class membership would generalize, and observed considerable overlap between pre-class and post-class gradients. These findings have led Fields et al (1997) to propose that the generalization of stimulus equivalence is a means by which conceptual classes merge with perceptual classes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The generalization of equivalence relations to a range of novel stimuli has been reported a number of times in studies utilizing verbally competent, adult human subjects (e.g., Fields, Adams, Buffington, Yang, & Verhave, 1996;Fields & Reeve, 2001;Fields, Reeve, Adams, Brown, & Verhave, 1997;Fields, Reeve, Adams, & Verhave, 1991;Rehfeldt, 2003;Rehfeldt & Hayes, 2000;Rehfeldt, Hayes, & Steele, 1998). This body of research has revealed that equivalence relations may generalize to dimensional variants that are physically similar along some dimension to an original training stimulus.…”
mentioning
confidence: 99%
“…An equivalence class should function as a network that occasions the transfer of new responses among class members or the generalization of equivalence-based responding to other stimuli (Barnes, Browne, Smeets, & Roche, 1995;Fields, Reeve , Adams, Brown , & Verhave , 1997;Sidman , 1994) . The cross-modal general ization tests provided one such assessment in the current experiment.…”
Section: Discussionmentioning
confidence: 99%